The Relationship Between Neutrophil-Lymphocyte Ratio (NLR), C-Reactive Protein (CRP), Interleukin 6 (IL-6), and D-Dimer Levels on the Severity of Covid-19 Patients at RSU Muhammadiyah University of Malang - Thahri Iskandar; Djoni Djunaedi; Silvana Gadis Ardhistix’s; Maulana Faishol Charisma M; Fajrul Falah; Muhammad Samir; Diah Hermayanti (Saintika Medika : Jurnal Ilmu Kesehatan dan Kedokteran Keluarga, 2023)
Background: COVID-19 virus infection has the potential to become severe in individuals who are susceptible or who have comorbid diseases. Natural immunity status in infected sufferers can cause an increase in the number of neutrophil cells and a decrease in the number of lymphocyte cells (increased neutrophil-lymphocyte ratio), serum inter-leukin-6 (IL-6), C-reactive protein (CRP) levels which are associated with severity. covid-19. Hypercoagulability that occurs in COVID-19 infection causes an increase in D-dimer levels, reflecting a response to prothrombotic phenomena and is associated with an increased risk of mortality in COVID-19 patients. Objective: To determine the relationship between Neutrophil-lymphocyte ratio (NLR), C-reactive protein (CRP), Interleukin-6 (IL-6), and D-dimer levels on the severity of Covid-19 patients at Muhammadiyah Malang University (UMM) Hospital Method: Using a retrospective design by taking a total sampling of medical record data for COVID-19 patients treated at UMM Hospital in 2021-2022. Results and Discussion: Spearman correlation on NLR 0.426 (p=0.000), OR=3.67, 95% CI=1.622-8.226, CRP 0.343 (p=0.000) with OR 5.143, 95%CI=1.128-23.448, D- Dimer 0.326 (p=0.000), OR 2.497, 95% CI=1.142-5.458. Meanwhile, the correlation and IL-6 estimation values could not be calculated because the sample size was insufficient. CRP levels in COVID-19 patients are the best predictor of worsening compared to other parameters. Conclusion: NLR values, CRP levels, and D-Dimer levels are related to the degree of severity in COVID-19 patients.